2017
DOI: 10.3324/haematol.2017.172544
|View full text |Cite
|
Sign up to set email alerts
|

Favorable impact of allogeneic stem cell transplantation in patients with therapy-related myelodysplasia regardless of TP53 mutational status

Abstract: Therapy-related myelodysplastic syndrome is a long-term complication of cancer treatment in patients receiving cytotoxic therapy, characterized by high-risk genetics and poor outcomes. Allogeneic hematopoietic cell transplantation is the only potential cure for this disease, but the prognostic impact of pre-transplant genetics and clinical features has not yet been fully characterized. We report here the genetic and clinical characteristics and outcomes of a relatively large cohort of patients with therapy-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…[1][2][3][4] The TP53 gene is located in the 17p13 chromosomal region and is 1 of the major tumor suppressor genes, often inactivated by deletion and/or mutation in many tumors, including hematologic malignancies. [5][6][7][8] TP53 mutations in AML and MDS are associated with significantly lower responses to standard chemotherapy and have emerged as a strong negative prognostic marker with poor treatment outcomes, 6,[8][9][10][11][12][13][14][15] including with ASCT. 3,4,8,[12][13][14] Here we hypothesized that outcomes of patients with TP53mutated AML/MDS are not uniformly poor and aimed to identify prognostic factors for survival in patients with TP53-mutated AML/MDS undergoing ASCT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The TP53 gene is located in the 17p13 chromosomal region and is 1 of the major tumor suppressor genes, often inactivated by deletion and/or mutation in many tumors, including hematologic malignancies. [5][6][7][8] TP53 mutations in AML and MDS are associated with significantly lower responses to standard chemotherapy and have emerged as a strong negative prognostic marker with poor treatment outcomes, 6,[8][9][10][11][12][13][14][15] including with ASCT. 3,4,8,[12][13][14] Here we hypothesized that outcomes of patients with TP53mutated AML/MDS are not uniformly poor and aimed to identify prognostic factors for survival in patients with TP53-mutated AML/MDS undergoing ASCT.…”
mentioning
confidence: 99%
“…Several studies have shown the ability of graft vs leukemia effect to overcome the poor prognosis in these patients after ASCT in CR1. 3,4,7 A recent European Society for Blood and Marrow Transplantation analysis showed that ASCT for patients in CR1 with 17P abnormality led to a 2-year OS of 28% and leukemiafree survival of 24%. The 2-year NRM was 15%, and the 2-year relapse incidence was 61%.…”
mentioning
confidence: 99%
“…The role of allogeneic transplant remains controversial for TP53 -mutated leukemia [ 140 , 141 ]. Practices vary dramatically among transplant centers—some do not recommend transplant to any patients with mutated TP53 , some recommend transplant only if a complete remission (CR) is achieved, and others recommend transplant in the absence of another viable alternative.…”
Section: Treatment Of Secondary Acute Myeloid Leukemia and Therapymentioning
confidence: 99%
“…This suggests that the escalation of the intensity of the conditioning regimen is ineffective in improving the outcomes of TP53 -mutated MDS patients [ 69 ]. However, controversial results were also reported, in which no significant difference in prognosis was found after transplantation between the MDS with or without TP53 mutations [ 71 ]. Yoshizato et al compared the prognosis of TP53 -mutant MDS in combination with complex karyotypes to patients with TP53 mutations but without complex karyotypes, and showed that the TP53 mutation-alone patients had a significantly better OS compared to those with both TP53 mutation and complex karyotypes [ 72 ].…”
Section: The Predictive Power Of Tp53 Mutations In the Current Standard Therapy Of Mdsmentioning
confidence: 99%